2007
DOI: 10.2166/wst.2007.788
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of carwash wastewater with hollow fiber membrane aided by enhanced coagulation and activated carbon treatments

Abstract: The particles from carwash wastewater were separated by a hollow fiber membrane aided by a enhanced coagulation and activated carbon. This study demonstrated that the addition of KMnO(4) to coagulant (PAC) could enhance the efficiency of coagulation, which helped reduce clogging of the ultrafiltration membrane and activated carbon. The existence of LAS can loosen the gel layer on the membrane and improve the flux. Adsorption of particles such as organic matter and oil is the main reason causing membrane flux d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, mean turbidity exceeded the criteria in China in both car washes. All quality parameters of outflow treated with hollow fiber membrane aided by enhanced coagulation and activated carbon treatments satisfied the criteria of China [5]. In a previous study (S.K., unpublished) high conductivity values were measured from purified water.…”
Section: Quality Of Reused Watermentioning
confidence: 78%
See 1 more Smart Citation
“…However, mean turbidity exceeded the criteria in China in both car washes. All quality parameters of outflow treated with hollow fiber membrane aided by enhanced coagulation and activated carbon treatments satisfied the criteria of China [5]. In a previous study (S.K., unpublished) high conductivity values were measured from purified water.…”
Section: Quality Of Reused Watermentioning
confidence: 78%
“…Waste waters from car washes consist of dirt from the cars like sand and dust, chemicals used for the washing, materials from washing equipment, as well as lubricants and other chemicals for maintaining the equipment [1]. Several applications have been developed and tested for treatment of car wash waste waters including for example ultrafiltration [4], nanofiltration [3], hollow fiber membranes [5], and electrochemical oxidation [6,7]. In Finland, there are around 900 automatic car washes, which are often located at petrol stations, and about 10 million cars are washed in these car washes every year.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that the use of other coagulants such as ferrous sulfate (Gönder et al 2017), poly aluminum chloride (Tang et al 2007;Tan & Tang 2008;Rodriguez Boluarte et al 2016), FeCl 3 (Tang et al 2007;Moazzem et al 2018) and Poly Aluminum Ferric Chloride (PAFC) (Zhang et al 2012) can be useful in CWW treatment, however, the efficiency of these coagulants vary. For example, (Tang et al 2007) reported that the efficiency for COD reduction by 25 mg/L Polyferric Sulfate (PFS) and Poly Aluminum Chloride (PAC) were determined to be higher than that for FeCl 3 , however, at the dosage of 40 mg/L, FeCl 3 had better COD reduction compared with PFS. The reason for the high removal of COD is likely due to inherent characteristics of PAC coagulant: high absorption of organic matter with a negative charge on the PAC flocs with a positive charge (Rodriguez Boluarte et al 2016).…”
Section: Coagulationmentioning
confidence: 99%
“…To improve the efficiency of the coagulation process in CWW treatment, advanced coagulation and cocoagulants have received much attention by researchers. For example, (Tang et al 2007;Tan & Tang 2008) reported that that the use of 1 to 1.5 mg/L of KMNO 4 as advanced coagulation before adding coagulant reduces turbidity by 5 mg/L due to the strong oxidation potential of this material on organic matter and the possibility of its hydrolysis to MNO 2 , which is an absorbent, oxidizing and packing effects. Furthermore, adding KMNO 4 before coagulant can reduce its effectiveness for flocs destruction and improve process efficiency in comparison with adding KMNO 4 after coagulant addition.…”
Section: Coagulationmentioning
confidence: 99%
See 1 more Smart Citation